The Internal Cranial Anatomy of a Female With Endocrine Disorders From a Mediaeval Population - Kubicka, Anna Maria; Charlier, Philippe; Balzeau, Antoine (Frontiers in Endocrinology, 2022)
Gigantism and acromegaly have been observed in past populations; however, analyses usually focus on the morphological features of the post-cranial skeleton. The aim of this study is to characterize the internal anatomical features of the skull (brain endocast anatomy and asymmetry, frontal pneumatization, cranial thickness, sella turcica size) of an adult individual from the 11-14th centuries with these two diseases, in comparison with non-pathological individuals from the same population. The material consisted of 33 adult skulls from a mediaeval population, one of them belonging to an adult female with endocrine disorders (OL-23/77). Based on the CT scans, the internal cranial anatomy was analysed. The sella turcica of Ol-23/77 is much larger than in the comparative sample. The endocast of the individual OL-23/77 shows a left frontal/left occipital petalia, while the comparative population mostly had right frontal/left occipital petalias. The asymmetry in petalia location in OL-23/77 comes within the range of variation observed in the comparative population. The individual has high values for cranial thickness. The frontal sinuses of the specimen analysed are similar in size and shape to the comparative sample only for data scaled to the skull length. Enlarged sella turcica is typical for individuals with acromegaly/gigantism. The pattern of the left frontal/left occipital petalia in the specimen OL-23/77 is quite rare. The position of the endocranial petalias has not influenced the degree of asymmetry in the specimen. Despite the large bone thickness values, skull of OL-23/77 does not show any abnormal features. The skull/endocast relationship in this individual shows some peculiarities in relation to its large size, while other internal anatomical features are within the normal range of variation of the comparative sample.